Reduced response of retinal vessel diameters to flicker stimulation in patients with diabetes. Issue 7 (17th June 2004) - Garhöfer, G; Zawinka, C; Resch, H; Kothy, P; Schmetterer, L; Dorner, G T
Abstract : Background/aim: Stimulation of the retina with flickering light increases retinal arterial and venous diameters in animals and humans, indicating a tight coupling between neural activity and blood flow. The aim of the present study was to investigate whether this response is altered in patients with insulin dependent diabetes mellitus. Methods: 26 patients with diabetes mellitus with no or mild non-proliferative retinopathy and 26 age and sex matched healthy volunteers were included in the study. Retinal vessel diameters were measured continuously with the Zeiss retinal vessel analyser. During these measurements three episodes of square wave flicker stimulation periods (16, 32, and 64 seconds; 8 Hz) were applied through the illumination pathway of the vessel analyser. Results: In retinal arteries, the response to stimulation with diffuse luminance flicker was significantly diminished in diabetic patients compared to healthy volunteers (ANOVA, p<0.0031). In non-diabetic controls flicker stimulation increased retinal arterial diameters by +1.6% (1.8%) (mean, p<0.001 v baseline), +2.8% (SD 2.2%) (p<0.001) and +2.8% (1.6%) (p<0.001) during 16, 32, and 64 seconds of flicker stimulation, respectively. In diabetic patients flicker had no effect on arterial vessel diameters: +0.1% (3.1%) (16 seconds, p = 0.9), +1.1% (2.7%) (32 seconds, p = 0.07), +1.0% (2.8%) (64 seconds, p = 0.1). In retinal veins, the response to flicker light was not significantly different in both groups. Retinal venous vessel diameters increased by +0.7% (1.6%) (16 seconds, p<0.05), +1.9% (2.3%) (32 seconds, p<0.001) and 1.7% (1.8%) (64 seconds, p<0.001) in controls during flicker stimulation. Again, no increase was observed in the patients group: +0.6% (2.4%), +0.5% (1.5%), and +1.2% (3.1%) (16, 32, and 64 seconds, respectively). Conclusion: Flicker responses of retinal arteries and veins are abnormally reduced in patients with IDDM with no or mild non-proliferative retinopathy. Whether this diminished response can be attributed to altered retinal vascular reactivity or to decreased neural activity has yet to be clarified.